Leadership strategies for Technological Advancement in Makassar City Governance - Suyuthi, Nurmadhani Fitri; Hamid, Mulyadi; Saputro, Lukasiwan Eddy (Journal of Management and Administration Provision, 2023)
This quantitative study investigates the connection between management strategies and technological development in Makassar City governance. Through a cross-sectional survey layout, statistics have been accrued from a representative sample of Makassar City government officers, specializing in demographic traits, perceptions of management techniques, and technological advancement. Descriptive facts analysis found out insights into the demographic profile of the sample, highlighting the significance of gender range, intergenerational collaboration, and inclusive selection-making techniques in governance. Furthermore, the analysis recognized transformational and visionary management as giant drivers of technological development, aligning with previous research emphasizing their superb effect on organizational overall performance and innovation. Respondents also expressed high perceptions of technological development, underscoring the growing popularity of technology's ability to enhance governance tactics and improve carrier shipping. These findings offer actionable insights for policymakers, practitioners, and researchers, emphasizing the significance of promoting powerful leadership and leveraging generation to pressure innovation and improvement in Makassar City.